2022
DOI: 10.1111/jan.15273
|View full text |Cite
|
Sign up to set email alerts
|

Psycho‐behavioural factors influencing COVID‐19 vaccine hesitancy among Korean adults: The moderating role of age

Abstract: Aims This study aimed to identify the psycho‐behavioural factors influencing coronavirus disease 2019 (COVID‐19) vaccine hesitancy among Korean adults. We examined the primary effects of eHealth literacy, social responsibility and self‐efficacy on COVID‐19 vaccine hesitancy using the information‐motivation‐behavioural skills (IMB) model. The moderating effect of age on the relationship between psycho‐behavioural factors and COVID‐19 vaccine hesitancy was also examined. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…Vaccinating the younger population against COVID-19 to block the transmission of SARS-CoV-2 in the community was a common advocacy for promoting the young population’s vaccination uptake [ 55 ]. However, our results suggest that older people value social responsibility more when making vaccination decisions, which was also identified in other contexts [ 56 , 57 ]. A previous study found that communicating prosocial benefits is effective in increasing multiple vaccination uptake in older adults [ 58 ].…”
Section: Discussionsupporting
confidence: 70%
“…Vaccinating the younger population against COVID-19 to block the transmission of SARS-CoV-2 in the community was a common advocacy for promoting the young population’s vaccination uptake [ 55 ]. However, our results suggest that older people value social responsibility more when making vaccination decisions, which was also identified in other contexts [ 56 , 57 ]. A previous study found that communicating prosocial benefits is effective in increasing multiple vaccination uptake in older adults [ 58 ].…”
Section: Discussionsupporting
confidence: 70%
“…The analysis of journals showed that Journal of Advanced Nursing have the most publications and citations, indicating that this journal has contributed much to the publication and knowledge dissemination about applying SEM in nursing researches (Demerouti et al, 2000;G. Y. Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Demographic variables play a substantial role in the intention to take COVID-19-related precautionary measures. For instance, age significantly moderates vaccine hesitancy towards COVID-19 [ 84 ]. H4 of this study validated that females are more susceptible to infodemics and conspiracy beliefs than males.…”
Section: Discussionmentioning
confidence: 99%